Analysis Of Economic Efficiency Of Egg Production In Imo State (Stochastic Frontier Approach) - Ehirim, N. C.; Essien, U. A.; Ikheloa, E.; Nwachukwu, E. U. (Advances in Social Sciences Research Journal, 2019)
The study applied a stochastic frontier cost function to analyze economic efficiency of poultry egg farmers and ascertained variation in economic efficiency due to inefficiency effects on egg production in Imo State. Multi-stage sampling was adopted to select 240 poultry egg farmers and data was analyzed using Stochastic Frontier Model. Flock size, costs of drugs and capital (depreciation) were significant factors of cost efficiency of the poultry egg farmers. The sigma squared (σ2) of 0.001 for the poultry farmers were statistically significant at 1% showing a goodness of fit of the model. The variance ratio (ɣ) estimated as 0.65 for the farmers were significant at 1% level which implied that 65% variations in the cost of production of the poultry egg farmers were due to the inefficiency factor (µi). The mean economic efficiency was 0.560 and ranges between 0.224 and 0.987. The coefficients of age of farmers and household size were positive while coefficients of years of access to credit, farming experience and flock size were negative and significant at 1% level of significance on economic inefficiency of egg producers. It can therefore be recommended that capital should be channeled to commercial poultry production through the provision of macro-credits and formulation of policies and programmes by the Government to direct financial institutions to grant a definite reasonable proportion of loan-able funds to commercial poultry farmers and Potent medicine and vaccine should be provided in sufficient quantities, easily accessible at cheaper costs.